Inconsistent idealizations and inferentialism about scientific representation. (October 2021) - Tan, Peter
Abstract: Inferentialists about scientific representation hold that an apparatus's representing a target system consists in the apparatus allowing "surrogative inferences" about the target. I argue that a serious problem for inferentialism arises from the fact that many scientific theories and models contain internal inconsistencies. Inferentialism, left unamended, implies that inconsistent scientific models have unlimited representational power, since an inconsistency permits any conclusion to be inferred. I consider a number of ways that inferentialists can respond to this challenge before suggesting my own solution. I develop an analogy to exploitable glitches in a game. Even though inconsistent representational apparatuses may in some sense allow for contradictions to be generated within them, doing so violates the intended function of the apparatus's parts and hence violates representational "gameplay".